PENGARUH HASIL-HASL UJIAN DI SEKOLAH TERHADAP HASIL UJIAN NASIONAL DI SMU NEGERI 1 LIMBOTO KABUPATEN GORONTALO - -, Noeryanti (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2009)
The aim of the research is to know whether the result of school examination in-fluences the result of national examination significantly. Observation data was taken from the third year science students of SMUN1 Limboto Gorontalo Regency Gorontalo Pro-vince. The best method to get regression model with unbias estimator is used the least square was done by using classical assumption examination, those are normal, multi-colinier an correlation ones. The result showed that national examination data, mean of Raport, Tryout, School examination marks and Practice examination, fulfill this assum-ption. Base on analysis data, it that in partially, UAN grades are influenced by: Raport grades with MSE=0,004 and R2=45.9%, Tryout grade with MSE= 0.09931 and R2= 59.3%, School grade with MSE=0.235691 and R2=5.8% and Practical grade with MSE=0.09931 dan R2 = 59.3%. Simultantly, UAN grades are influence by: Raport grade= –0.384, Tryout grade=0.848, School grades = –0.303 and Practical grade=0.082. Based on beta coefficient, it can be concluded that mean variable of tryout mark has the most dominant influences to national examination mark. The surtable mathematics model can be stated as Ŷ=4,985+ 0,182(x1)+0,370(x2)–0,261(x3)–0,280(x4)+0,376(lag_Y).